A Study on the Impact of Household Occupants’ Behavior on Energy Consumption Using an Integrated Computer Model - Lin, Yaolin; Yang, Wei; Gabriel, Kamiel S. (Frontiers in Built Environment, 2015)
In this paper, several models are integrated into a thermal model to study the impact of occupants’ behaviors on the building energy consumption. An air flow model is developed to simulate ventilation related to the occupant’s patterns of window opening and closing. An electric consumption model is developed to simulate the usage pattern and the electricity input to household electric appliances. The thermostat setpoint temperature and window shading schemes are varied with different occupants’ behavior norms and are included in the model. The simulation was applied to a typical household located in the city of Oshawa in Ontario, Canada. The results show that the window opening has the greatest impact on the energy consumption during the heating season, and the shading scheme has the greatest impact on the A/C energy consumption during the cooling season. The electricity consumption of the A/C can be significantly reduced by appropriately applying the shading and opening schemes and resetting the thermostat setpoint temperature to a slightly higher degree. Keeping the windows closed and allowing the solar radiation to be transmitted through the window in winter help reduce the energy usage to heat the house.